Chemical plating method for improving surface hardness of aluminum alloy
By plating doped particles-Ni-Cu-P composite plating on the surface of the aluminum alloy, the problems of low hardness and poor wear resistance of the aluminum alloy are solved, which significantly improves its corrosion resistance and wear resistance and reduces maintenance costs.
Patent Information
- Application Number
- CN202411777107.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The low hardness and poor wear resistance of aluminum alloys limit their application in industrial production.
An electroless plating method is adopted to coat a layer of doped particles-Ni-Cu-P composite plating layer on the surface of the aluminum alloy. The method includes plating an aqueous solution of aluminum nitrate in the reactor, adding urea and zirconium oxide nitrate, preparing the nanopowder solid phase through stirring, heating and calcining, and then soaking in hydrogen peroxide and dispersing ultrasonic stirring to form plating solution doped particles. Then, the aluminum alloy plate is picked up in a composite aqueous solution of nitric acid and phosphoric acid, and then treated in a specially prepared mother liquor and ethylenediamine ethanol solution to improve surface adsorption. Finally, plating is applied in the plating solution to form a dense plating layer.
It significantly improves the corrosion resistance and wear resistance of aluminum alloys, improves durability, and reduces maintenance costs. The self-corrosion potential of the surface of the aluminum alloy after plating is obviously positively shifted, and the Vickers hardness is significantly improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloy plating, and in particular to a chemical plating method for improving the surface hardness of an aluminum alloy. Background Art
[0002] Aluminum alloy has low density, excellent thermal and electrical conductivity, good plasticity, high specific strength, and can be treated on the surface. It is a metal material with excellent comprehensive performance. However, aluminum alloys usually have low hardness and poor wear resistance, which are subject to certain restrictions in industrial production. Chemical plating is also called electroless plating, which means that in the absence of an external current, the metal ions in the electrolyte solution are reduced on the surface of the active catalytic material with a reducing agent to deposit a metal coating that is firmly bonded to the substrate. The process of improving the surface hardness and wear resistance of aluminum alloys by chemical plating is of great significance. Summary of the invention
[0003] To this end, the present invention provides a chemical plating method for improving the surface hardness of aluminum alloy, the preparation steps comprising:
[0004] (1) preparing an aqueous solution of aluminum nitrate in a reaction kettle; stirring the aqueous solution of aluminum nitrate, then adding urea to the solution under stirring, continuing to stir the solution for more than 10 minutes after the addition is completed, then heating the solution to 50±5° C. in a water bath and keeping the temperature, then adding zirconium oxynitrate to the solution under stirring, continuing to stir the solution at a constant temperature of 50±5° C. for 4-5 minutes after the addition is completed, closing the reaction kettle, heating to 140-160° C. and keeping the temperature for 150-200 minutes, cooling naturally to room temperature after the insulation is completed, opening the reaction kettle, separating the solid from the liquid, washing the solid phase with deionized water for more than 3 times, then drying at 80° C. for more than 10 hours, and calcining at 550-580° C. for 3-4 hours after drying to obtain a nano powder solid phase;
[0005] (2) Soaking the nanopowder solid phase in hydrogen peroxide for more than 15 hours, then separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, drying at 80°C for more than 5 hours after washing, and then adding it to N,N-dimethylformamide with ultrasonic stirring and dispersion for 20 to 30 minutes to obtain a dispersion, heating the dispersion to 60±3°C in a water bath, and then adding succinic anhydride and 3-aminopropyltriethoxysilane to the dispersion under stirring, and continuing to stir the dispersion at 60±3°C for more than 5 hours after the addition is completed, separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, and drying at 80°C for more than 5 hours after washing to obtain plating solution-doped particles;
[0006] (3) preparing a composite aqueous solution of nitric acid and phosphoric acid, immersing the degreased aluminum alloy plate in the composite aqueous solution of nitric acid and phosphoric acid for 60 to 70 seconds for pickling, washing with deionized water to remove the surface acid after pickling, and drying the water stains on the surface of the aluminum alloy plate with a high-pressure air gun to obtain the pickled aluminum alloy plate;
[0007] (4) preparing an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride, adding hydrochloric acid to adjust the pH value of the solution to 8.5, and adding water to fix the volume to obtain a mother solution; preparing an ethanol solution of ethylenediamine; immersing the pickled aluminum alloy plate in acetone for cleaning, then taking it out and drying it at 80° C. for more than 2 hours to remove the acetone, and then immersing the aluminum alloy plate in the ethanol solution of ethylenediamine after drying, standing it for 20 hours, then taking it out, washing it with deionized water for more than 2 times, and drying it at 80° C. for more than 30 minutes; stirring the mother solution, and then adding riboflavin to the mother solution under stirring, continuing to stir for more than 10 minutes after the addition is completed, and then immersing it in the dried aluminum alloy plate, standing it for more than 15 hours, to obtain a modified aluminum alloy plate surface;
[0008] (5) preparing a plating solution, wherein the components of the plating solution include doped particles, thiourea, nickel sulfate, copper sulfate, sodium hypophosphite, ammonium acetate, trisodium citrate, and sodium dodecyl sulfate, and the solvent is water; adjusting the pH of the plating solution to 6 with hydrochloric acid or sodium hydroxide solution, then heating the plating solution to 80±2° C. in a water bath for insulation, and then immersing the surface of the aluminum alloy plate in the plating solution for plating for 90 to 100 minutes, subjecting the plating solution to magnetic stirring during the plating process, testing the pH of the plating solution every 10 minutes, and adjusting the pH of the plating solution to 6 with hydrochloric acid or sodium hydroxide solution; after plating, rinsing the surface of the aluminum alloy plate with deionized water to remove the plating solution, and drying with a high-pressure air gun to obtain an aluminum alloy with high surface hardness.
[0009] Furthermore, in the step (1), the concentration of aluminum nitrate in the aqueous solution of aluminum nitrate is 20-25 g / L, and the solvent is water; the volume ratio of the mass of the added urea and zirconyl nitrate to the aqueous solution of aluminum nitrate is urea: zirconyl nitrate: aqueous solution of aluminum nitrate = 4-5 g: 16-18 g: 1 L.
[0010] Furthermore, in the step (2), the mass percentage of the solute in the hydrogen peroxide is 30%; the mass ratio of the nano powder solid phase immersed in the hydrogen peroxide is nano powder solid phase: hydrogen peroxide = 1:200.
[0011] Furthermore, in the step (2), the ratio of the amount of N,N-dimethylformamide added to the dried solid phase is dried solid phase: N,N-dimethylformamide = 0.8-1 g: 100 mL; the ratio of the added mass of succinic anhydride and 3-aminopropyltriethoxysilane to the mass of the dried solid phase added when preparing the dispersion is succinic anhydride: 3-aminopropyltriethoxysilane: dried solid phase = 1.6-2 g: 25-30 g: 0.8-1 g.
[0012] Furthermore, in the step (3), in the composite aqueous solution of nitric acid and phosphoric acid, the concentration of nitric acid is 12-15 g / L, the concentration of phosphoric acid is 220-240 mg / L, and the solvent is water.
[0013] Furthermore, in the step (4), the mother liquor is prepared by first dissolving 121 g of tris(hydroxymethyl)aminomethane hydrochloride) in 600 mL of deionized water to prepare an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride, then adding 1 mol / L of hydrochloric acid to adjust the pH value of the solution to 8.5, and then adding deionized water to make the volume to 1 L to obtain the mother liquor.
[0014] Furthermore, in the step (4), the mass percentage of ethylenediamine in the ethanol solution of ethylenediamine is 20%, and the solvent is ethanol; the mass ratio of the added riboflavin to the mother liquor is riboflavin: mother liquor = 200-260 mg: 1 L.
[0015] Furthermore, in step (5), the concentrations of the components in the plating solution are: 1-2 g / L of doped particles, 0.5 mg / L of thiourea, 24-26 g / L of nickel sulfate, 0.5-0.8 g / L of copper sulfate, 22-24 g / L of sodium hypophosphite, 18-20 g / L of ammonium acetate, 24-25 g / L of trisodium citrate, 1-2 mg / L of sodium dodecyl sulfate, and the solvent is water; the mass percentage of hydrochloric acid solute used to adjust the pH of the plating solution is 30%, the mass percentage of sodium hydroxide solution solute is 30%, and the solvent is water.
[0016] The beneficial effect of the present invention is that: the process of the present invention is to plate a layer of doped particles-Ni-Cu-P composite coating on the surface of the aluminum alloy, and the coating significantly improves the corrosion resistance and wear resistance of the aluminum alloy, improves durability, and reduces maintenance costs. The self-corrosion potential of the aluminum alloy surface after plating is significantly positively shifted, and the Vickers hardness is significantly improved. This is mainly because the present invention first synthesizes zirconium-doped aluminum oxide particles to further enhance the hardness of the doped particles, while refining the particle size and increasing the specific surface area of the doped particles, so that after subsequent plating in the coating, the doped particles are finer and denser, the overall density of the coating is improved, the corrosion resistance is improved, and the fine particles are conducive to improving the wear resistance of the coating, which is manifested as an increase in microhardness. In the subsequent process, hydrogen peroxide is used to increase the hydroxyl content on the surface of the doped particles, and then carboxylation is performed to form carboxyl groups; on the other hand, amino groups and hydrophilic riboflavin hydrophilic functional groups are loaded on the surface of the aluminum alloy plate to improve the adsorption of the surface of the aluminum alloy plate and promote the formation of the coating; and the surface groups of the doped particles and the surface groups of the aluminum alloy plate interact with each other, which improves the binding of the doped particles and the surface of the aluminum alloy plate during the plating process, which is conducive to the entry of the doped particles into the coating. In addition, the doped particles promote the nucleation of the coating during the plating process, refine the grain size of the coating, improve the density and stability of the coating, and use the fine grain strengthening and second phase strengthening effects to simultaneously improve the corrosion resistance and surface hardness of the coating itself. DETAILED DESCRIPTION
[0017] The present invention will be further described below in conjunction with the embodiments.
[0018] Example 1
[0019] A chemical plating method for improving the surface hardness of an aluminum alloy, the preparation steps comprising:
[0020] (1) preparing an aqueous solution of aluminum nitrate in a reactor, wherein the concentration of aluminum nitrate in the aqueous solution is 20 g / L and the solvent is water; stirring the aqueous solution of aluminum nitrate, then adding urea to the solution under stirring, continuing to stir the solution for 10 minutes after the addition is completed, then heating the solution to 50±5° C. in a water bath to keep the temperature, and then adding zirconium oxynitrate to the solution under stirring, wherein the mass ratio of the added urea and zirconium oxynitrate to the aqueous solution of aluminum nitrate is urea: zirconium oxynitrate: aqueous solution of aluminum nitrate = 4 g: 16 g: 1 L; continuing to stir the solution at a constant temperature of 50±5° C. for 5 minutes after the addition is completed, closing the reactor, heating to 150° C. to keep the temperature for 180 minutes, cooling naturally to room temperature after the end of the heat preservation, opening the reactor, separating the solid from the liquid, washing the solid phase with deionized water for 3 times, then drying at 80° C. for 10 hours, and calcining at 560° C. for 3 hours after drying to obtain a nano powder solid phase;
[0021] (2) The nanopowder solid phase is immersed in hydrogen peroxide for 15 hours, wherein the mass percentage of the solute in the hydrogen peroxide is 30%; the mass ratio of the nanopowder solid phase immersed in hydrogen peroxide is nanopowder solid phase: hydrogen peroxide = 1:200; then the solid and liquid are separated, the solid phase is washed with deionized water for 3 times, and after washing, it is dried at 80° C. for 5 hours, and then added to N,N-dimethylformamide and stirred and dispersed under ultrasonic environment for 20 minutes to obtain a dispersion liquid, and the amount ratio of N,N-dimethylformamide added to the dried solid phase is dried solid phase: N,N-dimethylformamide = 0.8 g: 100 mL ; The dispersion is heated to 60±3°C in a water bath and kept warm, and then succinic anhydride and 3-aminopropyltriethoxysilane are added to the dispersion under stirring, and the mass ratio of the added mass of succinic anhydride and 3-aminopropyltriethoxysilane to the dried solid phase added when preparing the dispersion is succinic anhydride: 3-aminopropyltriethoxysilane: dried solid phase = 1.6g: 25g: 0.8g; After the addition is completed, the dispersion is continued to be stirred at 60±3°C for 5h, the solid-liquid separation is carried out, the solid phase is washed 3 times with deionized water, and after washing, it is dried at 80°C for 5h to obtain the plating solution doped particles;
[0022] (3) preparing a composite aqueous solution of nitric acid and phosphoric acid, wherein the concentration of nitric acid is 12 g / L, the concentration of phosphoric acid is 220 mg / L, and the solvent is water; immersing (submerging the entire aluminum alloy plate) the degreased aluminum alloy plate (made of 2A12 aluminum alloy, and all embodiments and comparative examples use plates from the same batch that are completely identical) in the composite aqueous solution of nitric acid and phosphoric acid for 60 seconds for pickling, washing with deionized water to remove the surface acid after pickling, and drying the water stains on the surface of the aluminum alloy plate with a high-pressure air gun to obtain the pickled aluminum alloy plate;
[0023] (4) preparing an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride, adding hydrochloric acid to adjust the pH value of the solution to 8.5, and adding water to make up the volume to obtain a mother solution; the preparation method of the mother solution is specifically as follows: first dissolving 121 g of tris(hydroxymethyl)aminomethane hydrochloride in 600 mL of deionized water to prepare an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride), then adding 1 mol / L of hydrochloric acid to adjust the pH value of the solution to 8.5, and adding deionized water to make up the volume to 1 L to obtain the mother solution; preparing an ethanol solution of ethylenediamine; in the ethanol solution of ethylenediamine, the mass percentage of ethylenediamine is 20%, and the solvent is ethanol; immersing the pickled aluminum alloy plate in water; Soak (immerse the entire aluminum alloy plate) in acetone for cleaning, then take out and dry at 80°C for 2h to remove the acetone, and then soak the aluminum alloy plate in the ethanol solution of ethylenediamine (immerse the entire aluminum alloy plate) after drying, let it stand for 20h, then take it out, wash it twice with deionized water, and dry it at 80°C for 30min; stir the mother liquor, and then add riboflavin to the mother liquor under stirring, the mass ratio of the added riboflavin to the volume ratio of the mother liquor is riboflavin: mother liquor = 200mg: 1L; continue stirring for 10min after the addition is completed, then immerse the dried aluminum alloy plate, let it stand for 15h, and obtain the surface of the aluminum alloy plate;
[0024] (5) preparing a plating solution, wherein the components of the plating solution are doped particles, thiourea, nickel sulfate, copper sulfate, sodium hypophosphite, ammonium acetate, trisodium citrate, and sodium dodecyl sulfate, and the solvent is water; the concentrations of the components in the plating solution are: 1 g / L doped particles, 0.5 mg / L thiourea, 24 g / L nickel sulfate, 0.5 g / L copper sulfate, 22 g / L sodium hypophosphite, 18 g / L ammonium acetate, 24 g / L trisodium citrate, and 1 mg / L sodium dodecyl sulfate, and the solvent is water; adjusting the pH of the plating solution to 6 with hydrochloric acid or sodium hydroxide solution, and then plating The liquid is heated to 80±2° C. in a water bath for insulation. After insulation, the surface of the aluminum alloy plate is immersed in the plating solution for plating for 90 minutes. During the plating process, the plating solution is magnetically stirred, the pH of the plating solution is tested every 10 minutes, and the pH of the plating solution is adjusted to 6 with hydrochloric acid or sodium hydroxide solution; the mass percentage of the hydrochloric acid solute used to adjust the pH of the plating solution is 30%, the mass percentage of the sodium hydroxide solution solute is 30%, and the solvent is water; after plating, the surface of the aluminum alloy plate is rinsed with deionized water to remove the plating solution, and the plate is dried with a high-pressure air gun to obtain an aluminum alloy with high surface hardness.
[0025] Example 2
[0026] A chemical plating method for improving the surface hardness of an aluminum alloy, the preparation steps comprising:
[0027] (1) preparing an aqueous solution of aluminum nitrate in a reactor, wherein the concentration of aluminum nitrate in the aqueous solution is 22 g / L and the solvent is water; stirring the aqueous solution of aluminum nitrate, then adding urea to the solution under stirring, continuing to stir the solution for 10 minutes after the addition is completed, then heating the solution to 50±5° C. in a water bath to keep the temperature, and then adding zirconium oxynitrate to the solution under stirring, wherein the mass ratio of the added urea and zirconium oxynitrate to the aqueous solution of aluminum nitrate is urea: zirconium oxynitrate: aqueous solution of aluminum nitrate = 4 g: 17 g: 1 L; continuing to stir the solution at a constant temperature of 50±5° C. for 5 minutes after the addition is completed, closing the reactor, heating to 150° C. to keep the temperature for 180 minutes, cooling naturally to room temperature after the end of the heat preservation, opening the reactor, separating the solid from the liquid, washing the solid phase with deionized water for 3 times, then drying at 80° C. for 10 hours, and calcining at 560° C. for 3 hours after drying to obtain a nano powder solid phase;
[0028] (2) The nanopowder solid phase is immersed in hydrogen peroxide for 15 hours, wherein the mass percentage of the solute in the hydrogen peroxide is 30%; the mass ratio of the nanopowder solid phase immersed in hydrogen peroxide is nanopowder solid phase: hydrogen peroxide = 1:200; then the solid and liquid are separated, the solid phase is washed with deionized water for 3 times, dried at 80° C. for 5 hours after washing, and then added to N,N-dimethylformamide and stirred and dispersed under ultrasonic environment for 20 minutes to obtain a dispersion liquid, and the amount ratio of N,N-dimethylformamide added to the dried solid phase is dried solid phase: N,N-dimethylformamide = 0.9 g: 100 mL ; The dispersion is heated to 60±3°C in a water bath and kept warm, and then succinic anhydride and 3-aminopropyltriethoxysilane are added to the dispersion under stirring, and the mass ratio of the added mass of succinic anhydride and 3-aminopropyltriethoxysilane to the dried solid phase added when preparing the dispersion is succinic anhydride: 3-aminopropyltriethoxysilane: dried solid phase = 1.8g: 26g: 0.9g; After the addition is completed, the dispersion is continued to be stirred at 60±3°C for 5h, the solid-liquid separation is carried out, the solid phase is washed 3 times with deionized water, and after washing, it is dried at 80°C for 5h to obtain the plating solution doped particles;
[0029] (3) preparing a composite aqueous solution of nitric acid and phosphoric acid, wherein the concentration of nitric acid is 12 g / L, the concentration of phosphoric acid is 220 mg / L, and the solvent is water; immersing the degreased aluminum alloy plate (made of 2A12 aluminum alloy) (immersing the entire aluminum alloy plate) in the composite aqueous solution of nitric acid and phosphoric acid for 60 seconds for pickling, washing with deionized water to remove the surface acid after pickling, and drying the water stains on the surface of the aluminum alloy plate with a high-pressure air gun to obtain the pickled aluminum alloy plate;
[0030] (4) preparing an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride, adding hydrochloric acid to adjust the pH value of the solution to 8.5, and adding water to make up the volume to obtain a mother solution; the preparation method of the mother solution is specifically as follows: first dissolving 121 g of tris(hydroxymethyl)aminomethane hydrochloride in 600 mL of deionized water to prepare an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride), then adding 1 mol / L of hydrochloric acid to adjust the pH value of the solution to 8.5, and adding deionized water to make up the volume to 1 L to obtain the mother solution; preparing an ethanol solution of ethylenediamine; in the ethanol solution of ethylenediamine, the mass percentage of ethylenediamine is 20%, and the solvent is ethanol; immersing the pickled aluminum alloy plate in water; Soak (immerse the entire aluminum alloy plate) in acetone for cleaning, then take out and dry at 80°C for 2h to remove the acetone, and then soak the aluminum alloy plate in the ethanol solution of ethylenediamine (immerse the entire aluminum alloy plate) after drying, let it stand for 20h, then take it out, wash it twice with deionized water, and dry it at 80°C for 30min; stir the mother liquor, and then add riboflavin to the mother liquor under stirring, the mass ratio of the added riboflavin to the volume ratio of the mother liquor is riboflavin: mother liquor = 220mg: 1L; continue stirring for 10min after the addition is completed, then immerse the dried aluminum alloy plate, let it stand for 15h, and obtain the surface of the aluminum alloy plate;
[0031] (5) preparing a plating solution, wherein the components of the plating solution are doped particles, thiourea, nickel sulfate, copper sulfate, sodium hypophosphite, ammonium acetate, trisodium citrate, and sodium dodecyl sulfate, and the solvent is water; the concentrations of the components in the plating solution are: 1 g / L doped particles, 0.5 mg / L thiourea, 25 g / L nickel sulfate, 0.6 g / L copper sulfate, 22 g / L sodium hypophosphite, 18 g / L ammonium acetate, 24 g / L trisodium citrate, and 1 mg / L sodium dodecyl sulfate, and the solvent is water; adjusting the pH of the plating solution to 6 with hydrochloric acid or sodium hydroxide solution, and then plating The liquid is heated to 80±2° C. in a water bath for insulation. After insulation, the surface of the aluminum alloy plate is immersed in the plating solution for plating for 90 minutes. During the plating process, the plating solution is magnetically stirred, the pH of the plating solution is tested every 10 minutes, and the pH of the plating solution is adjusted to 6 with hydrochloric acid or sodium hydroxide solution; the mass percentage of the hydrochloric acid solute used to adjust the pH of the plating solution is 30%, the mass percentage of the sodium hydroxide solution solute is 30%, and the solvent is water; after plating, the surface of the aluminum alloy plate is rinsed with deionized water to remove the plating solution, and the plate is dried with a high-pressure air gun to obtain an aluminum alloy with high surface hardness.
[0032] Example 3
[0033] A chemical plating method for improving the surface hardness of an aluminum alloy, the preparation steps comprising:
[0034] (1) preparing an aqueous solution of aluminum nitrate in a reactor, wherein the concentration of aluminum nitrate in the aqueous solution is 24 g / L and the solvent is water; stirring the aqueous solution of aluminum nitrate, then adding urea to the solution under stirring, continuing to stir the solution for 10 minutes after the addition is completed, then heating the solution to 50±5° C. in a water bath to keep the temperature, and then adding zirconium oxynitrate to the solution under stirring, wherein the mass ratio of the added urea and zirconium oxynitrate to the aqueous solution of aluminum nitrate is urea: zirconium oxynitrate: aqueous solution of aluminum nitrate = 5 g: 17 g: 1 L; continuing to stir the solution at a constant temperature of 50±5° C. for 5 minutes after the addition is completed, closing the reactor, heating to 150° C. to keep the temperature for 180 minutes, cooling naturally to room temperature after the end of the heat preservation, opening the reactor, separating the solid from the liquid, washing the solid phase with deionized water for 3 times, then drying at 80° C. for 10 hours, and calcining at 560° C. for 3 hours after drying to obtain a nano powder solid phase;
[0035] (2) The nanopowder solid phase is immersed in hydrogen peroxide for 15 hours, wherein the mass percentage of the solute in the hydrogen peroxide is 30%; the mass ratio of the nanopowder solid phase immersed in hydrogen peroxide is nanopowder solid phase: hydrogen peroxide = 1:200; then the solid and liquid are separated, the solid phase is washed with deionized water for 3 times, dried at 80° C. for 5 hours after washing, and then added to N,N-dimethylformamide and stirred and dispersed under ultrasonic environment for 20 minutes to obtain a dispersion liquid, and the amount ratio of N,N-dimethylformamide added to the dried solid phase is dried solid phase: N,N-dimethylformamide = 0.9 g: 100 mL ; The dispersion is heated to 60±3°C in a water bath and kept warm, and then succinic anhydride and 3-aminopropyltriethoxysilane are added to the dispersion under stirring, and the mass ratio of the added mass of succinic anhydride and 3-aminopropyltriethoxysilane to the dried solid phase added when preparing the dispersion is succinic anhydride: 3-aminopropyltriethoxysilane: dried solid phase = 1.8g: 28g: 0.9g; After the addition is completed, the dispersion is continued to be stirred at 60±3°C for 5h, the solid-liquid separation is carried out, the solid phase is washed with deionized water for 3 times, and the washing is completed and dried at 80°C for 5h to obtain the plating solution doped particles;
[0036] (3) preparing a composite aqueous solution of nitric acid and phosphoric acid, wherein the concentration of nitric acid is 12 g / L, the concentration of phosphoric acid is 220 mg / L, and the solvent is water; immersing the degreased aluminum alloy plate (made of 2A12 aluminum alloy) (immersing the entire aluminum alloy plate) in the composite aqueous solution of nitric acid and phosphoric acid for 60 seconds for pickling, washing with deionized water to remove the surface acid after pickling, and drying the water stains on the surface of the aluminum alloy plate with a high-pressure air gun to obtain the pickled aluminum alloy plate;
[0037] (4) preparing an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride, adding hydrochloric acid to adjust the pH value of the solution to 8.5, and adding water to make up the volume to obtain a mother solution; the preparation method of the mother solution is specifically as follows: first dissolving 121 g of tris(hydroxymethyl)aminomethane hydrochloride in 600 mL of deionized water to prepare an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride), then adding 1 mol / L of hydrochloric acid to adjust the pH value of the solution to 8.5, and adding deionized water to make up the volume to 1 L to obtain the mother solution; preparing an ethanol solution of ethylenediamine; in the ethanol solution of ethylenediamine, the mass percentage of ethylenediamine is 20%, and the solvent is ethanol; immersing the pickled aluminum alloy plate in water; Soak (immerse the entire aluminum alloy plate) in acetone for cleaning, then take out and dry at 80°C for 2h to remove the acetone, and then soak the aluminum alloy plate in the ethanol solution of ethylenediamine (immerse the entire aluminum alloy plate) after drying, let it stand for 20h, then take it out, wash it twice with deionized water, and dry it at 80°C for 30min; stir the mother liquor, and then add riboflavin to the mother liquor under stirring, the mass ratio of the added riboflavin to the volume ratio of the mother liquor is riboflavin: mother liquor = 240mg: 1L; continue stirring for 10min after the addition is completed, then immerse the dried aluminum alloy plate, let it stand for 15h, and obtain the surface of the aluminum alloy plate;
[0038] (5) preparing a plating solution, wherein the components of the plating solution are doped particles, thiourea, nickel sulfate, copper sulfate, sodium hypophosphite, ammonium acetate, trisodium citrate, and sodium dodecyl sulfate, and the solvent is water; the concentrations of the components in the plating solution are: 2 g / L doped particles, 0.5 mg / L thiourea, 25 g / L nickel sulfate, 0.7 g / L copper sulfate, 24 g / L sodium hypophosphite, 20 g / L ammonium acetate, 25 g / L trisodium citrate, and 2 mg / L sodium dodecyl sulfate, and the solvent is water; adjusting the pH of the plating solution to 6 with hydrochloric acid or sodium hydroxide solution, and then plating The liquid is heated to 80±2° C. in a water bath for insulation. After insulation, the surface of the aluminum alloy plate is immersed in the plating solution for plating for 90 minutes. During the plating process, the plating solution is magnetically stirred, the pH of the plating solution is tested every 10 minutes, and the pH of the plating solution is adjusted to 6 with hydrochloric acid or sodium hydroxide solution; the mass percentage of the hydrochloric acid solute used to adjust the pH of the plating solution is 30%, the mass percentage of the sodium hydroxide solution solute is 30%, and the solvent is water; after plating, the surface of the aluminum alloy plate is rinsed with deionized water to remove the plating solution, and the plate is dried with a high-pressure air gun to obtain an aluminum alloy with high surface hardness.
[0039] Example 4
[0040] A chemical plating method for improving the surface hardness of an aluminum alloy, the preparation steps comprising:
[0041] (1) preparing an aqueous solution of aluminum nitrate in a reactor, wherein the concentration of aluminum nitrate in the aqueous solution is 25 g / L and the solvent is water; stirring the aqueous solution of aluminum nitrate, then adding urea to the solution under stirring, and continuing to stir the solution for 10 minutes after the addition is completed, and then heating the solution to 50±5° C. in a water bath to keep the temperature, and then adding zirconium oxynitrate to the solution under stirring, wherein the mass ratio of the added urea and zirconium oxynitrate to the aqueous solution of aluminum nitrate is urea: zirconium oxynitrate: aqueous solution of aluminum nitrate = 5 g: 18 g: 1 L; continuing to stir the solution at a constant temperature of 50±5° C. for 5 minutes after the addition is completed, closing the reactor, heating to 150° C. and keeping the temperature for 180 minutes, cooling naturally to room temperature after the end of the insulation, opening the reactor, separating the solid from the liquid, washing the solid phase with deionized water for 3 times, and then drying at 80° C. for 10 hours, and calcining at 560° C. for 3 hours after drying to obtain a nano powder solid phase;
[0042] (2) The nanopowder solid phase is immersed in hydrogen peroxide for 15 hours, wherein the mass percentage of the solute in the hydrogen peroxide is 30%; the mass ratio of the nanopowder solid phase immersed in hydrogen peroxide is nanopowder solid phase: hydrogen peroxide = 1:200; then the solid and liquid are separated, the solid phase is washed with deionized water for 3 times, dried at 80° C. for 5 hours after the washing, and then added to N,N-dimethylformamide and stirred and dispersed under ultrasonic environment for 20 minutes to obtain a dispersion liquid, and the amount ratio of N,N-dimethylformamide added to the dried solid phase is dried solid phase: N,N-dimethylformamide = 1g: 100m L; the dispersion is heated to 60±3°C in a water bath and kept warm, and then succinic anhydride and 3-aminopropyltriethoxysilane are added to the dispersion under stirring, and the mass ratio of the added mass of succinic anhydride and 3-aminopropyltriethoxysilane to the dried solid phase added when preparing the dispersion is succinic anhydride: 3-aminopropyltriethoxysilane: dried solid phase = 2g: 30g: 1g; after the addition is completed, the dispersion is continued to be kept warm and stirred at 60±3°C for 5h, the solid-liquid separation is carried out, the solid phase is washed 3 times with deionized water, and after washing, it is dried at 80°C for 5h to obtain plating solution doped particles;
[0043] (3) preparing a composite aqueous solution of nitric acid and phosphoric acid, wherein the concentration of nitric acid is 12 g / L, the concentration of phosphoric acid is 220 mg / L, and the solvent is water; immersing the degreased aluminum alloy plate (made of 2A12 aluminum alloy) (immersing the entire aluminum alloy plate) in the composite aqueous solution of nitric acid and phosphoric acid for 60 seconds for pickling, washing with deionized water to remove the surface acid after pickling, and drying the water stains on the surface of the aluminum alloy plate with a high-pressure air gun to obtain the pickled aluminum alloy plate;
[0044] (4) preparing an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride, adding hydrochloric acid to adjust the pH value of the solution to 8.5, and adding water to make up the volume to obtain a mother solution; the preparation method of the mother solution is specifically as follows: first dissolving 121 g of tris(hydroxymethyl)aminomethane hydrochloride in 600 mL of deionized water to prepare an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride), then adding 1 mol / L of hydrochloric acid to adjust the pH value of the solution to 8.5, and adding deionized water to make up the volume to 1 L to obtain the mother solution; preparing an ethanol solution of ethylenediamine; in the ethanol solution of ethylenediamine, the mass percentage of ethylenediamine is 20%, and the solvent is ethanol; immersing the pickled aluminum alloy plate in water; Soak (immerse the entire aluminum alloy plate) in acetone for cleaning, then take out and dry at 80°C for 2h to remove the acetone, and then soak the aluminum alloy plate in the ethanol solution of ethylenediamine (immerse the entire aluminum alloy plate) after drying, let it stand for 20h, then take it out, wash it twice with deionized water, and dry it at 80°C for 30min; stir the mother liquor, and then add riboflavin to the mother liquor under stirring, the mass ratio of the added riboflavin to the volume ratio of the mother liquor is riboflavin: mother liquor = 260mg: 1L; continue stirring for 10min after the addition is completed, then immerse the dried aluminum alloy plate, let it stand for 15h, and obtain the surface of the aluminum alloy plate;
[0045] (5) preparing a plating solution, wherein the components of the plating solution are doped particles, thiourea, nickel sulfate, copper sulfate, sodium hypophosphite, ammonium acetate, trisodium citrate, and sodium dodecyl sulfate, and the solvent is water; the concentrations of the components in the plating solution are: 2 g / L doped particles, 0.5 mg / L thiourea, 26 g / L nickel sulfate, 0.8 g / L copper sulfate, 24 g / L sodium hypophosphite, 20 g / L ammonium acetate, 25 g / L trisodium citrate, and 2 mg / L sodium dodecyl sulfate, and the solvent is water; adjusting the pH of the plating solution to 6 with hydrochloric acid or sodium hydroxide solution, and then plating The liquid is heated to 80±2° C. in a water bath for insulation. After insulation, the surface of the aluminum alloy plate is immersed in the plating solution for plating for 90 minutes. During the plating process, the plating solution is magnetically stirred, the pH of the plating solution is tested every 10 minutes, and the pH of the plating solution is adjusted to 6 with hydrochloric acid or sodium hydroxide solution; the mass percentage of the hydrochloric acid solute used to adjust the pH of the plating solution is 30%, the mass percentage of the sodium hydroxide solution solute is 30%, and the solvent is water; after plating, the surface of the aluminum alloy plate is rinsed with deionized water to remove the plating solution, and the plate is dried with a high-pressure air gun to obtain an aluminum alloy with high surface hardness.
[0046] Comparative Example 1
[0047] A method for preparing a comparative test aluminum alloy plate, the preparation steps comprising:
[0048] (1) preparing a composite aqueous solution of nitric acid and phosphoric acid, wherein the concentration of nitric acid is 12 g / L, the concentration of phosphoric acid is 220 mg / L, and the solvent is water; immersing (submerging the entire aluminum alloy plate) the degreased aluminum alloy plate in the composite aqueous solution of nitric acid and phosphoric acid for 60 seconds for pickling, washing with deionized water to remove the surface acid after pickling, and drying the water stains on the surface of the aluminum alloy plate with a high-pressure air gun to obtain the pickled aluminum alloy plate;
[0049] (2) preparing an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride), adding hydrochloric acid to adjust the pH value of the solution to 8.5, and adding water to make up the volume to obtain a mother solution; the preparation method of the mother solution is specifically as follows: first dissolving 121 g of tris(hydroxymethyl)aminomethane hydrochloride in 600 mL of deionized water to prepare an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride), then adding 1 mol / L of hydrochloric acid to adjust the pH value of the solution to 8.5, and adding deionized water to make up the volume to 1 L to obtain the mother solution; preparing an ethanol solution of ethylenediamine; in the ethanol solution of ethylenediamine, the mass percentage of ethylenediamine is 20%, and the solvent is ethanol; immersing the pickled aluminum alloy plate in water; Soak (immerse the entire aluminum alloy plate) in acetone for cleaning, then take out and dry at 80°C for 2h to remove the acetone, and then soak the aluminum alloy plate in the ethanol solution of ethylenediamine (immerse the entire aluminum alloy plate) after drying, let it stand for 20h, then take it out, wash it twice with deionized water, and dry it at 80°C for 30min; stir the mother liquor, and then add riboflavin to the mother liquor under stirring, the mass ratio of the added riboflavin to the volume ratio of the mother liquor is riboflavin: mother liquor = 240mg: 1L; continue stirring for 10min after the addition is completed, then immerse the dried aluminum alloy plate, let it stand for 15h, and obtain the surface of the aluminum alloy plate;
[0050] (3) preparing a plating solution, wherein the components of the plating solution are thiourea, nickel sulfate, copper sulfate, sodium hypophosphite, ammonium acetate, trisodium citrate, and sodium dodecyl sulfate, and the solvent is water; the concentrations of the components in the plating solution are: thiourea 0.5 mg / L, nickel sulfate 25 g / L, copper sulfate 0.7 g / L, sodium hypophosphite 24 g / L, ammonium acetate 20 g / L, trisodium citrate 25 g / L, sodium dodecyl sulfate 2 mg / L, and the solvent is water; adjusting the pH of the plating solution to 6 with hydrochloric acid or sodium hydroxide solution, and then heating the plating solution in a water bath to 80 ± 40 °C; The aluminum alloy plate is kept warm at 2°C, and after the heat preservation, the surface of the aluminum alloy plate is immersed in the plating solution for plating for 90 minutes, the plating solution is magnetically stirred during the plating process, the pH of the plating solution is tested every 10 minutes, and the pH of the plating solution is adjusted to 6 with hydrochloric acid or sodium hydroxide solution; the mass percentage of the hydrochloric acid solute used to adjust the pH of the plating solution is 30%, the mass percentage of the sodium hydroxide solution solute is 30%, and the solvent is water; after the plating is completed, the plating solution on the surface of the aluminum alloy plate is rinsed with deionized water to remove the plating solution, and the plate is dried with a high-pressure air gun to obtain the test aluminum alloy plate described in this comparative example.
[0051] Comparative Example 2
[0052] A method for preparing a comparative test aluminum alloy plate, the preparation steps comprising:
[0053] (1) an aqueous solution of aluminum nitrate is prepared in a reactor, wherein the concentration of aluminum nitrate in the aqueous solution is 24 g / L and the solvent is water; the aqueous solution of aluminum nitrate is stirred, and then urea is added to the solution under stirring, and the solution is stirred for 10 min after the addition is completed, and then heated in a water bath to 50±5° C. and the solution is stirred for 5 min, and the volume ratio of the added urea to the aqueous solution of aluminum nitrate is urea: aqueous solution of aluminum nitrate = 5 g: 1 L; the reactor is closed, heated to 150° C. and kept warm for 180 min, and naturally cooled to room temperature after the end of the insulation, the reactor is opened, the solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and then dried at 80° C. for 10 h, and then calcined at 560° C. for 3 h to obtain the nano powder solid phase of this comparative example;
[0054] (2) The nanopowder solid phase is immersed in hydrogen peroxide for 15 hours, wherein the mass percentage of the solute in the hydrogen peroxide is 30%; the mass ratio of the nanopowder solid phase immersed in hydrogen peroxide is nanopowder solid phase: hydrogen peroxide = 1:200; then the solid and liquid are separated, the solid phase is washed with deionized water for 3 times, dried at 80° C. for 5 hours after washing, and then added to N,N-dimethylformamide and stirred and dispersed under ultrasonic environment for 20 minutes to obtain a dispersion liquid, and the amount ratio of N,N-dimethylformamide added to the dried solid phase is dried solid phase: N,N-dimethylformamide = 0.9 g: 100 mL ; The dispersion is heated to 60±3°C in a water bath and kept warm, and then succinic anhydride and 3-aminopropyltriethoxysilane are added to the dispersion under stirring, and the mass ratio of the added mass of succinic anhydride and 3-aminopropyltriethoxysilane to the dried solid phase added when preparing the dispersion is succinic anhydride: 3-aminopropyltriethoxysilane: dried solid phase = 1.8g: 28g: 0.9g; After the addition is completed, the dispersion is continued to be stirred at 60±3°C for 5h, the solid-liquid separation is carried out, the solid phase is washed with deionized water for 3 times, and the washing is completed and dried at 80°C for 5h to obtain the plating solution doped particles;
[0055] (3) preparing a composite aqueous solution of nitric acid and phosphoric acid, wherein the concentration of nitric acid is 12 g / L, the concentration of phosphoric acid is 220 mg / L, and the solvent is water; immersing the degreased aluminum alloy plate (made of 2A12 aluminum alloy) (immersing the entire aluminum alloy plate) in the composite aqueous solution of nitric acid and phosphoric acid for 60 seconds for pickling, washing with deionized water to remove the surface acid after pickling, and drying the water stains on the surface of the aluminum alloy plate with a high-pressure air gun to obtain the pickled aluminum alloy plate;
[0056] (4) preparing an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride, adding hydrochloric acid to adjust the pH value of the solution to 8.5, and adding water to make up the volume to obtain a mother solution; the preparation method of the mother solution is specifically as follows: first dissolving 121 g of tris(hydroxymethyl)aminomethane hydrochloride in 600 mL of deionized water to prepare an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride), then adding 1 mol / L of hydrochloric acid to adjust the pH value of the solution to 8.5, and adding deionized water to make up the volume to 1 L to obtain the mother solution; preparing an ethanol solution of ethylenediamine; in the ethanol solution of ethylenediamine, the mass percentage of ethylenediamine is 20%, and the solvent is ethanol; immersing the pickled aluminum alloy plate in water; Soak (immerse the entire aluminum alloy plate) in acetone for cleaning, then take out and dry at 80°C for 2h to remove the acetone, and then soak the aluminum alloy plate in the ethanol solution of ethylenediamine (immerse the entire aluminum alloy plate) after drying, let it stand for 20h, then take it out, wash it twice with deionized water, and dry it at 80°C for 30min; stir the mother liquor, and then add riboflavin to the mother liquor under stirring, the mass ratio of the added riboflavin to the volume ratio of the mother liquor is riboflavin: mother liquor = 240mg: 1L; continue stirring for 10min after the addition is completed, then immerse the dried aluminum alloy plate, let it stand for 15h, and obtain the surface of the aluminum alloy plate;
[0057] (5) preparing a plating solution, wherein the components of the plating solution are doped particles, thiourea, nickel sulfate, copper sulfate, sodium hypophosphite, ammonium acetate, trisodium citrate, and sodium dodecyl sulfate, and the solvent is water; the concentrations of the components in the plating solution are: 2 g / L doped particles, 0.5 mg / L thiourea, 25 g / L nickel sulfate, 0.7 g / L copper sulfate, 24 g / L sodium hypophosphite, 20 g / L ammonium acetate, 25 g / L trisodium citrate, and 2 mg / L sodium dodecyl sulfate, and the solvent is water; adjusting the pH of the plating solution to 6 with hydrochloric acid or sodium hydroxide solution, and then The bath is heated to 80±2° C. and kept warm. After keeping warm, the surface of the aluminum alloy plate is immersed in the plating solution for plating for 90 minutes. During the plating process, the plating solution is magnetically stirred, the pH of the plating solution is tested every 10 minutes, and the pH of the plating solution is adjusted to 6 with hydrochloric acid or sodium hydroxide solution; the mass percentage of the hydrochloric acid solute used to adjust the pH of the plating solution is 30%, the mass percentage of the sodium hydroxide solution solute is 30%, and the solvent is water; after the plating is completed, the plating solution on the surface of the aluminum alloy plate is rinsed with deionized water to remove the plating solution, and the plate is dried with a high-pressure air gun to obtain the test aluminum alloy plate described in this comparative example.
[0058] Comparative Example 3
[0059] A method for preparing a comparative test aluminum alloy plate, the preparation steps comprising:
[0060] (1) preparing an aqueous solution of aluminum nitrate in a reactor, wherein the concentration of aluminum nitrate in the aqueous solution is 24 g / L and the solvent is water; stirring the aqueous solution of aluminum nitrate, then adding urea to the solution under stirring, continuing to stir the solution for 10 minutes after the addition is completed, then heating the solution to 50±5° C. in a water bath to keep the temperature, and then adding zirconium oxynitrate to the solution under stirring, wherein the mass ratio of the added urea and zirconium oxynitrate to the aqueous solution of aluminum nitrate is urea: zirconium oxynitrate: aqueous solution of aluminum nitrate = 5 g: 17 g: 1 L; continuing to stir the solution at a constant temperature of 50±5° C. for 5 minutes after the addition is completed, closing the reactor, heating to 150° C. to keep the temperature for 180 minutes, cooling naturally to room temperature after the end of the heat preservation, opening the reactor, separating the solid from the liquid, washing the solid phase with deionized water for 3 times, then drying at 80° C. for 10 hours, and calcining at 560° C. for 3 hours after drying to obtain a nano powder solid phase;
[0061] (2) the nano powder solid phase was immersed in hydrogen peroxide for 15 hours, the mass percentage of the solute in the hydrogen peroxide was 30%; the mass ratio of the nano powder solid phase immersed in hydrogen peroxide was nano powder solid phase: hydrogen peroxide = 1:200; then the solid and liquid were separated, the solid phase was washed with deionized water for 3 times, and after washing, it was dried at 80° C. for 5 hours to obtain the plating solution doped particles of this comparative example;
[0062] (3) preparing a composite aqueous solution of nitric acid and phosphoric acid, wherein the concentration of nitric acid is 12 g / L, the concentration of phosphoric acid is 220 mg / L, and the solvent is water; immersing the degreased aluminum alloy plate (made of 2A12 aluminum alloy) (immersing the entire aluminum alloy plate) in the composite aqueous solution of nitric acid and phosphoric acid for 60 seconds for pickling, washing with deionized water to remove the surface acid after pickling, and drying the water stains on the surface of the aluminum alloy plate with a high-pressure air gun to obtain the pickled aluminum alloy plate;
[0063] (4) preparing an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride, adding hydrochloric acid to adjust the pH value of the solution to 8.5, and adding water to make up the volume to obtain a mother solution; the preparation method of the mother solution is specifically as follows: first dissolving 121 g of tris(hydroxymethyl)aminomethane hydrochloride in 600 mL of deionized water to prepare an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride), then adding 1 mol / L of hydrochloric acid to adjust the pH value of the solution to 8.5, and adding deionized water to make up the volume to 1 L to obtain the mother solution; preparing an ethanol solution of ethylenediamine; in the ethanol solution of ethylenediamine, the mass percentage of ethylenediamine is 20%, and the solvent is ethanol; immersing the pickled aluminum alloy plate in water; Soak (immerse the entire aluminum alloy plate) in acetone for cleaning, then take out and dry at 80°C for 2h to remove the acetone, and then soak the aluminum alloy plate in the ethanol solution of ethylenediamine (immerse the entire aluminum alloy plate) after drying, let it stand for 20h, then take it out, wash it twice with deionized water, and dry it at 80°C for 30min; stir the mother liquor, and then add riboflavin to the mother liquor under stirring, the mass ratio of the added riboflavin to the volume ratio of the mother liquor is riboflavin: mother liquor = 240mg: 1L; continue stirring for 10min after the addition is completed, then immerse the dried aluminum alloy plate, let it stand for 15h, and obtain the surface of the aluminum alloy plate;
[0064] (5) preparing a plating solution, wherein the components of the plating solution are doped particles, thiourea, nickel sulfate, copper sulfate, sodium hypophosphite, ammonium acetate, trisodium citrate, and sodium dodecyl sulfate, and the solvent is water; the concentrations of the components in the plating solution are: 2 g / L doped particles, 0.5 mg / L thiourea, 25 g / L nickel sulfate, 0.7 g / L copper sulfate, 24 g / L sodium hypophosphite, 20 g / L ammonium acetate, 25 g / L trisodium citrate, and 2 mg / L sodium dodecyl sulfate, and the solvent is water; adjusting the pH of the plating solution to 6 with hydrochloric acid or sodium hydroxide solution, and then The bath is heated to 80±2° C. and kept warm. After keeping warm, the surface of the aluminum alloy plate is immersed in the plating solution for plating for 90 minutes. During the plating process, the plating solution is magnetically stirred, the pH of the plating solution is tested every 10 minutes, and the pH of the plating solution is adjusted to 6 with hydrochloric acid or sodium hydroxide solution; the mass percentage of the hydrochloric acid solute used to adjust the pH of the plating solution is 30%, the mass percentage of the sodium hydroxide solution solute is 30%, and the solvent is water; after the plating is completed, the plating solution on the surface of the aluminum alloy plate is rinsed with deionized water to remove the plating solution, and the plate is dried with a high-pressure air gun to obtain the test aluminum alloy plate described in this comparative example.
[0065] Comparative Example 4
[0066] A method for preparing a comparative test aluminum alloy plate, the preparation steps comprising:
[0067] (1) preparing an aqueous solution of aluminum nitrate in a reactor, wherein the concentration of aluminum nitrate in the aqueous solution is 24 g / L and the solvent is water; stirring the aqueous solution of aluminum nitrate, then adding urea to the solution under stirring, and continuing to stir the solution for 10 minutes after the addition is completed, and then heating the solution to 50±5° C. in a water bath to keep the temperature, and then adding zirconium oxynitrate to the solution under stirring, wherein the mass ratio of the added urea and zirconium oxynitrate to the aqueous solution of aluminum nitrate is urea: zirconium oxynitrate: aqueous solution of aluminum nitrate = 5 g: 17 g: 1 L; continuing to stir the solution at a constant temperature of 50±5° C. for 5 minutes after the addition is completed, closing the reactor, heating to 150° C. and keeping the temperature for 180 minutes, cooling naturally to room temperature after the end of the keeping temperature, opening the reactor, separating the solid from the liquid, washing the solid phase with deionized water for 3 times, and then drying at 80° C. for 10 hours, and calcining at 560° C. for 3 hours after drying to obtain a nano powder solid phase;
[0068] (2) The nanopowder solid phase is immersed in hydrogen peroxide for 15 hours, wherein the mass percentage of the solute in the hydrogen peroxide is 30%; the mass ratio of the nanopowder solid phase immersed in hydrogen peroxide is nanopowder solid phase: hydrogen peroxide = 1:200; then the solid and liquid are separated, the solid phase is washed with deionized water for 3 times, dried at 80° C. for 5 hours after washing, and then added to N,N-dimethylformamide and stirred and dispersed under ultrasonic environment for 20 minutes to obtain a dispersion liquid, and the amount ratio of N,N-dimethylformamide added to the dried solid phase is dried solid phase: N,N-dimethylformamide = 0.9 g: 100 mL ; The dispersion is heated to 60±3°C in a water bath and kept warm, and then succinic anhydride and 3-aminopropyltriethoxysilane are added to the dispersion under stirring, and the mass ratio of the added mass of succinic anhydride and 3-aminopropyltriethoxysilane to the dried solid phase added when preparing the dispersion is succinic anhydride: 3-aminopropyltriethoxysilane: dried solid phase = 1.8g: 28g: 0.9g; After the addition is completed, the dispersion is continued to be stirred at 60±3°C for 5h, the solid-liquid separation is carried out, the solid phase is washed with deionized water for 3 times, and the washing is completed and dried at 80°C for 5h to obtain the plating solution doped particles;
[0069] (3) preparing a composite aqueous solution of nitric acid and phosphoric acid, wherein the concentration of nitric acid is 12 g / L, the concentration of phosphoric acid is 220 mg / L, and the solvent is water; immersing the degreased aluminum alloy plate (made of 2A12 aluminum alloy) (immersing the entire aluminum alloy plate) in the composite aqueous solution of nitric acid and phosphoric acid for 60 seconds for pickling, washing with deionized water to remove the surface acid after pickling, and drying the water stains on the surface of the aluminum alloy plate with a high-pressure air gun to obtain the pickled aluminum alloy plate;
[0070] (4) preparing a plating solution, wherein the components of the plating solution are doped particles, thiourea, nickel sulfate, copper sulfate, sodium hypophosphite, ammonium acetate, trisodium citrate, and sodium dodecyl sulfate, and the solvent is water; the concentrations of the components in the plating solution are: 2 g / L doped particles, 0.5 mg / L thiourea, 25 g / L nickel sulfate, 0.7 g / L copper sulfate, 24 g / L sodium hypophosphite, 20 g / L ammonium acetate, 25 g / L trisodium citrate, and 2 mg / L sodium dodecyl sulfate, and the solvent is water; adjusting the pH of the plating solution to 6 with hydrochloric acid or sodium hydroxide solution, and then placing the plating solution in a water bath. The plate was heated to 80±2° C. and kept warm. After keeping warm, the pickled aluminum alloy plate was immersed in the plating solution for plating for 90 minutes. During the plating process, the plating solution was magnetically stirred. The pH of the plating solution was tested every 10 minutes. The pH of the plating solution was adjusted to 6 with hydrochloric acid or sodium hydroxide solution. The mass percentage of the hydrochloric acid solute used to adjust the pH of the plating solution was 30%, the mass percentage of the sodium hydroxide solution solute was 30%, and the solvent was water. After the plating was completed, the plating solution on the surface of the aluminum alloy plate was rinsed with deionized water to remove the plating solution, and the plate was dried with a high-pressure air gun to obtain the test aluminum alloy plate described in this comparative example.
[0071] Example 5
[0072] The microhardness of the surface of the aluminum alloy plate prepared by the methods described in the above embodiments and comparative examples was tested using a microhardness tester, with a loading load of 2N and a loading time of 5s; 5 points were randomly selected for testing on each sample and the average value was taken. The self-corrosion potential of the aluminum alloy plate prepared by the methods described in the above embodiments and comparative examples was tested on an electrochemical workstation. The aluminum alloy plate was cut by wire to form a plated area of 1 cm 2 The test piece only exposes 1cm of the plated surface 2 The remaining surfaces were coated with glue to form the working electrode. The test adopted a three-electrode system, with a platinum electrode as the auxiliary electrode, a test sample as the working electrode, a saturated calomel electrode as the reference electrode, and a test solution of 3.5% sodium chloride aqueous solution. The scanning speed was 1mV / s, and the scanning range was -2 to 0.5V. The results are shown in Table 1.
[0073] As can be seen from Table 1, the process of the present invention is to plate a layer of doped particles-Ni-Cu-P composite coating on the surface of traditional aluminum alloy, and the coating significantly improves the corrosion resistance and wear resistance of the aluminum alloy, improves durability, and reduces maintenance costs. The self-corrosion potential of the aluminum alloy surface after plating is significantly positively shifted, and the Vickers hardness is significantly improved. This is mainly because the present invention first synthesizes zirconium-doped aluminum oxide particles to further enhance the hardness of the doped particles, while refining the particle size and increasing the specific surface area of the doped particles, so that after subsequent plating in the coating, the doped particles are finer and denser, the overall density of the coating is improved, and the corrosion resistance is improved. In addition, the fine particles are conducive to improving the wear resistance of the coating, which is manifested as an increase in microhardness. In the subsequent process, hydrogen peroxide is used to increase the hydroxyl content on the surface of the doped particles, and then carboxylation is performed to form carboxyl groups; on the other hand, amino groups and hydrophilic riboflavin hydrophilic functional groups are loaded on the surface of the aluminum alloy plate to improve the adsorption of the surface of the aluminum alloy plate and promote the formation of the coating; and the surface groups of the doped particles and the surface groups of the aluminum alloy plate interact with each other, which improves the binding of the doped particles and the surface of the aluminum alloy plate during the plating process, which is conducive to the entry of the doped particles into the coating. In addition, the doped particles promote the nucleation of the coating during the plating process, refine the grain size of the coating, improve the density and stability of the coating, and use the fine grain strengthening and second phase strengthening effects to simultaneously improve the corrosion resistance and surface hardness of the coating itself.
[0074] Table 1
[0075] Experimental Group Self-corrosion potential (V) Vickers hardness (HV) Example 1 -0.511 447 Example 2 -0.504 456 Example 3 -0.497 462 Example 4 -0.501 459 Comparative Example 1 -0.625 321 Comparative Example 2 -0.558 403 Comparative Example 3 -0.589 430 Comparative Example 4 -0.580 426 Control group -0.872 115
[0076] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A chemical plating method for improving the surface hardness of aluminum alloy, characterized in that the steps include: (1) preparing an aqueous solution of aluminum nitrate in a reaction kettle; stirring the aqueous solution of aluminum nitrate, then adding urea to the solution under stirring, continuing to stir the solution for more than 10 minutes after the addition is completed, then heating the solution to 50±5° C. in a water bath and keeping the temperature, then adding zirconium oxynitrate to the solution under stirring, continuing to stir the solution at a constant temperature of 50±5° C. for 4-5 minutes after the addition is completed, closing the reaction kettle, heating to 140-160° C. and keeping the temperature for 150-200 minutes, cooling naturally to room temperature after the insulation is completed, opening the reaction kettle, separating the solid from the liquid, washing the solid phase with deionized water for more than 3 times, then drying at 80° C. for more than 10 hours, and calcining at 550-580° C. for 3-4 hours after drying to obtain a nano powder solid phase; (2) Soaking the nanopowder solid phase in hydrogen peroxide for more than 15 hours, then separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, drying at 80°C for more than 5 hours after washing, and then adding it to N,N-dimethylformamide with ultrasonic stirring and dispersion for 20 to 30 minutes to obtain a dispersion, heating the dispersion to 60±3°C in a water bath, and then adding succinic anhydride and 3-aminopropyltriethoxysilane to the dispersion under stirring, and continuing to stir the dispersion at 60±3°C for more than 5 hours after the addition is completed, separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, and drying at 80°C for more than 5 hours after washing to obtain plating solution-doped particles; (3) preparing a composite aqueous solution of nitric acid and phosphoric acid, immersing the degreased aluminum alloy plate in the composite aqueous solution of nitric acid and phosphoric acid for 60 to 70 seconds for pickling, washing with deionized water to remove the surface acid after pickling, and drying the water stains on the surface of the aluminum alloy plate with a high-pressure air gun to obtain the pickled aluminum alloy plate; (4) preparing an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride, adding hydrochloric acid to adjust the pH value of the solution to 8.5, and adding water to fix the volume to obtain a mother solution; preparing an ethanol solution of ethylenediamine; immersing the pickled aluminum alloy plate in acetone for cleaning, then taking it out and drying it at 80° C. for more than 2 hours to remove the acetone, and then immersing the aluminum alloy plate in the ethanol solution of ethylenediamine after drying, standing it for 20 hours, then taking it out, washing it with deionized water for more than 2 times, and drying it at 80° C. for more than 30 minutes; stirring the mother solution, and then adding riboflavin to the mother solution under stirring, continuing to stir for more than 10 minutes after the addition is completed, and then immersing it in the dried aluminum alloy plate, standing it for more than 15 hours, to obtain a modified aluminum alloy plate surface; (5) preparing a plating solution, wherein the components of the plating solution include doped particles, thiourea, nickel sulfate, copper sulfate, sodium hypophosphite, ammonium acetate, trisodium citrate, and sodium dodecyl sulfate, and the solvent is water; adjusting the pH of the plating solution to 6 with hydrochloric acid or sodium hydroxide solution, then heating the plating solution to 80±2° C. in a water bath for insulation, and then immersing the surface of the aluminum alloy plate in the plating solution for plating for 90 to 100 minutes, subjecting the plating solution to magnetic stirring during the plating process, testing the pH of the plating solution every 10 minutes, and adjusting the pH of the plating solution to 6 with hydrochloric acid or sodium hydroxide solution; after plating, rinsing the surface of the aluminum alloy plate with deionized water to remove the plating solution, and drying with a high-pressure air gun to obtain an aluminum alloy with high surface hardness.
2. The chemical plating method for improving the surface hardness of aluminum alloy according to claim 1, characterized in that: In the step (1), the concentration of aluminum nitrate in the aqueous solution of aluminum nitrate is 20-25 g / L, and the solvent is water; the volume ratio of the mass of the added urea and zirconyl nitrate to the aqueous solution of aluminum nitrate is urea: zirconyl nitrate: aqueous solution of aluminum nitrate = 4-5 g: 16-18 g: 1 L.
3. The chemical plating method for improving the surface hardness of aluminum alloy according to claim 1, characterized in that: In the step (2), the mass percentage of the solute in the hydrogen peroxide is 30%; the mass ratio of the nano powder solid phase immersed in the hydrogen peroxide is nano powder solid phase: hydrogen peroxide = 1:
200.
4. The chemical plating method for improving the surface hardness of aluminum alloy according to claim 1, characterized in that: In the step (2), the ratio of the amount of N,N-dimethylformamide added to the dried solid phase is dried solid phase: N,N-dimethylformamide = 0.8-1 g: 100 mL; the ratio of the added mass of succinic anhydride and 3-aminopropyltriethoxysilane to the mass of the dried solid phase added when preparing the dispersion is succinic anhydride: 3-aminopropyltriethoxysilane: dried solid phase = 1.6-2 g: 25-30 g: 0.8-1 g.
5. The chemical plating method for improving the surface hardness of aluminum alloy according to claim 1, characterized in that: In the step (3), in the composite aqueous solution of nitric acid and phosphoric acid, the concentration of nitric acid is 12-15 g / L, the concentration of phosphoric acid is 220-240 mg / L, and the solvent is water.
6. The chemical plating method for improving the surface hardness of aluminum alloy according to claim 1, characterized in that: In the step (4), the mother liquor is prepared by first dissolving 121 g of tris(hydroxymethyl)aminomethane hydrochloride) in 600 mL of deionized water to prepare an aqueous solution of tris(hydroxymethyl)aminomethane hydrochloride, then adding 1 mol / L of hydrochloric acid to adjust the pH value of the solution to 8.5, and then adding deionized water to make the volume to 1 L to obtain the mother liquor.
7. The chemical plating method for improving the surface hardness of aluminum alloy according to claim 1, characterized in that: In the step (4), the mass percentage of ethylenediamine in the ethanol solution of ethylenediamine is 20%, and the solvent is ethanol; the mass ratio of the added riboflavin to the mother liquor is riboflavin: mother liquor = 200-260 mg: 1 L.
8. The chemical plating method for improving the surface hardness of aluminum alloy according to claim 1, characterized in that: In the step (5), the concentrations of the components in the plating solution are: 1-2 g / L of doped particles, 0.5 mg / L of thiourea, 24-26 g / L of nickel sulfate, 0.5-0.8 g / L of copper sulfate, 22-24 g / L of sodium hypophosphite, 18-20 g / L of ammonium acetate, 24-25 g / L of trisodium citrate, 1-2 mg / L of sodium dodecyl sulfate, and the solvent is water; the mass percentage of hydrochloric acid solute used to adjust the pH of the plating solution is 30%, the mass percentage of sodium hydroxide solution solute is 30%, and the solvent is water.